"Being Born like This, I Have No Right to Make Anybody Listen to Me": Understanding Different Forms of Stigma among Thai Transgender Women Living with HIV in Thailand. Issue 14 (6th December 2021) - de Lind van Wijngaarden, Jan W.; Fongkaew, Kangwan
ABSTRACT: This study explores the ways Thai transgender women are affected by internalized, perceived, vicarious and enacted stigma. Participants were eleven Thai transgender women living with HIV, who were asked about experiences of stigma in their daily lives. Various forms of verbal, psychological and physical harassment were reported. Internalized stigma and stigma within the transgender community itself were significant. Participants tended not to blame their family members or others in their social structure for their experiences of stigma. They tended to see the solution to tackle the problem of stigma mainly in changes in the behavior of transgender women themselves. This paper suggests that transgender people themselves should better understand how the structure, culture and institutions of mainstream society instill, reinforce and perpetuate stigma against, within and among them. There is a need for advocacy directed toward manifesting societal emancipation of Thai transgender people—starting with legal reform.